2015
DOI: 10.1387/ijdb.150280dr
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis and hyperbaric oxygen in the chick embryo chorioallantoic membrane

Abstract: Hyperbaric Oxygen Therapy (HBOT) is increasingly applied in different areas of medical practice. The oxy-hyperbarism effects are not well understood in cancer malignancy. One unique feature of cancer is the presence of hypoxic regions that are insensitive to conventional therapies. It is possible to alter the hypoxic state and produce reactive oxygen species for better treatment outcome by HBOT. In the present study, we determined the effects of HBOT on angiogenesis, a signature of cancer progression, by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Indeed, Chan and Burggren (2005) have shown that CAM mass is unchanged by hypoxia experienced during early or mid-development, but CAM mass at E18 is greatly increased by hypoxia. Despite these contrasting results, the present study is in agreement with that presented by Montecorboli et al (2015) where significantly higher CAM vascularization and an increased number of blood vessels were found for E6 and E7 subjected to HBOT (protocol: 2.0 ATA, for 30 min).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Indeed, Chan and Burggren (2005) have shown that CAM mass is unchanged by hypoxia experienced during early or mid-development, but CAM mass at E18 is greatly increased by hypoxia. Despite these contrasting results, the present study is in agreement with that presented by Montecorboli et al (2015) where significantly higher CAM vascularization and an increased number of blood vessels were found for E6 and E7 subjected to HBOT (protocol: 2.0 ATA, for 30 min).…”
Section: Discussionsupporting
confidence: 92%
“…In the literature, several studies extensively explore the effects of hypoxia and hyperoxia on CAM development. However, most of these studies (with the exception of Montecorboli et al, 2015 ) do not evaluate both the effects of pressure and oxygen concentration on embryonic development ( Dusseau and Hutchins, 1988 ; Burton and Palmer, 1992 ; Druyan and Levi, 2012 ). Interestingly, there is conflicting evidence of the effect of ambient oxygen on vascular development.…”
Section: Discussionmentioning
confidence: 99%
“…64,65 Because of its easy accessibility, the chicken CAM (frequently used as an experimental model, also as an alternative to the animal model, as just mentioned) has been used, in the present study, for the investigation of the angiogenic potential of SO. [66][67][68] Moreover, in the development stages used in this experimentation (from day 8 to day 12) the immunocompetent chicken system is not fully developed and for this reason it is not responsive to an exogenous material. 69 The angiogenic potential of the SO was evaluated by the CAM assay, incubating firstly SO and subsequently media conditioned by SOs.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms of actions needed further investigations, briefly NOS levels were increased in genomic and protein levels as well [20]. In-depth micro-array analyses of microvascular endothelial cells' genome proved huge impact of HBOT on angiogenesis-related gene expressions [21]. In these studies, HBOT dramatically increased tube formation capacity of endothelial cells on Matrigel [22].…”
Section: Endothelial Cells Angiogenesismentioning
confidence: 99%